Improved Thermoelectric Performance of In‐Doped Quaternary Cu2MnSnSe4 Alloys. Issue 6 (30th March 2022) - Mehmood, Fahad; Sun, Yuqing; Su, Wenbin; Chebanova, Galina; Zhai, Jinze; Wang, Long; Khan, Mahwish; Romanenko, Anatoly; Wang, Hongchao; Wang, Chunlei
Abstract : Recently, Cu2 MnSnSe4 alloys and similar compounds have drawn immense attention due to their low intrinsic thermal conductivity. However, their inferior electrical properties hinder their industrial applications. Herein, Cu2 MnSn1− x In x Se4 alloys are successfully synthesized and the thermoelectric transport properties are investigated. The results reveal that In doping significantly enhances the electrical properties by reducing electrical resistivity by 4.3 times at maximum temperature. As a consequence, the power factor value is enhanced to 665 μW K −2  m −1 for the sample with 7.5% In concentration which is about 2.2 times higher than the pristine sample. Eventually improved dimensionless figure of merit of 0.33 has been obtained for 5% sample. Abstract : Highest figure of merit of 0.33 has been achieved at 673 K for Cu2 MnSn0.95 In0.05 Se4, which is about 2 times higher than the parent sample, attributing increased power factor and charge carrier concentration through indium doping.